Islamic Stocks and Russia – Ukraine War: Evidence from the Jakarta Islamic Index - Erna Listyaningsih; Amirul Mukminin; Lenny Marzulina; Kasinyo Harto; Muhammad Rachmad; Muazza Muazza (Qubahan Academic Journal)
Previous research revealed that non-economic variables affected stock returns. War is one of the non-economic factors. All international stock markets were under pressure because of the conflict between Russia and Ukraine. The purpose of this study was to investigate returns and the liquidity of Jakarta Islamic Index (JII) stocks around the President Putin’s announcement the war Russia – Ukraine on 24th of February 2022 using an event study. JII stocks are sharia-compliant stocks with a high market capitalization, high level of liquidity, and low volatility. According to these findings, even though the abnormal return had a significant negative on the sixth day before the event date, the paired sample t test indicated that the abnormal return was not significant. However, JII's liquidity was significantly impacted on this shock. This demonstrates that the incident had little effect on the price of JII stocks. These characteristics lead to the prediction that the JII be able to withstand this shock. This study also has practical implications for investors, such as taking external shocks into account when selecting stocks.